PENGARUH HIPNOSIS LIMA JARI (H5J) DAN RELAKSASI OTOT PROGRESIF (ROP) TERHADAP ZOOM FATIGUE SISWA SMK KESEHATAN BINTANG PERSADA DENPASAR SELAMA PANDEMI COVID - - Yudhawati NLP S; Dewi Asri Made; Serinadi Made Desak (Journal of Nursing Care and Biomolecular, 2022)
Introduction: The Covid-19 Pandemic Situation has influenced almost all countries in the world and the life sector. The Indonesian government issued a policy of "social and physical distraction" and carried out all activities and delays out of the house (stay at home), in order to prevent the spread of COVID-19. However, this policy raises new problems in the field of education, especially in the learning process for students. The transfer of learning from synchronous to Asynchronous routinely using video calls or video conferences causes symptoms of fatigue and at risk of experiencing zoom fatigue. Zoom Fatigue handling strategies have not been focused on self -management independently through non -pharmacological thoughts and actions. Implementation of five fingers hypnotic (H5J) and progressive muscle relaxation (ROP) will increase the achievement of intervention so that it is more effective in reducing or eliminating the symptoms of zoom fatigue in students. Several H5J and ROP studies are significantly effective in reducing the level of anxiet. H5J and ROP are one of the high relaxation techniques, it will reduce stress and stress of mind. Selection of safe relaxation techniques without using chemicals, simple processes and becomes a highly recommended nursing intervention in care care for anxiety. Method: Quantitative research that uses the design of a pretest-posttest group at SMK Bintang Persada Denpasar Gangan Learning time from June to July 2022. The population in the Denalah study of all students as many as 86 to check. Samples of all sample students. The sample uses the specified purposive sampling criteria. Results and analysis: The results of the study that there is an effect of giving H5J and ROP to the fatigue zoom. Suggestions are expected to be more routine to train H5J and ROP to reduce the symptoms of the felt fatigue zoom. Keywords: Covid -19; H5J and ROP; Student, Zoom Fatique